Fistula between the right coronary artery and the branch of the pulmonary artery as an uncommon cause of syncope in elderly patients - Dutra Junior, Valdir Borges; Rosa, Andressa Stella Kuhn Correia da; Costa, Bruna Polanski; Pasetto, Camila Nunes Venâncio; Dalmas, Gabriela Graça Soder; Marion, Josiele Rossato; Lampert, Melissa Agostini (Medicina (Ribeirao Preto), 2017)
Coronary artery fistulas are uncommon and are consist in direct connections from both arteries or just from one of them with other structure. When they have low output, they usually tend to communicate with any of the cardiac chambers or other adjacent cardiac vessels. However, communications with the pulmonary trunk are rare and underdiagnosed, since most of patients are asymptomatic or have nonspecific symptoms related to the condition. In this report, we describe and discuss the case of a patient with a recurrent history of syncope, that started clinical follow-up in an ambulatory of geriatric and gerontology, whose investigation lead to the identification of an underlying cardiac cause as the etiology of the episodes.